Ensuring end-to-end privacy in IoT-based healthcare systems through hyperledger fabric and identity mixer - Maryam Nasr Esfahani; Behrouz Shahgholi Ghahfarokhi; Shahram Etemadi Borujeni (PLoS ONE, 2026)
Healthcare information is often sensitive and confidential, and any unauthorized disclosure can jeopardize patient privacy. Centralized approaches currently used to protect patient information are vulnerable to a single point of failure and the risk of data breaches from central servers. Conversely, distributed blockchain-based methods tend to focus only on safeguarding data privacy for certain segments of the communication path from sensors to end users. This leaves a gap in methodologies that ensure both location and data privacy throughout the entire communication from sensors to healthcare data users via blockchain technology. In this paper, we propose using Hyperledger Fabric to ensure the immutability of patient data and to address the single point of failure issue. Additionally, to maintain end-to-end data and location privacy, our proposed scheme integrates the Idemix protocol suit alongside Hyperledger Fabric and employs a lightweight communication protocol for interactions between healthcare sensors and gateways. Compared to previous methods, our approach not only facilitates privacy features such as patient anonymity and untraceability but also guarantees data integrity, confidentiality, mutual authentication, and resilience against a variety of security threats, including collusion among internal entities. While the implementation of blockchain may introduce additional computational overhead for service providers compared to centralized systems, this trade-off is outweighed by the significant enhancements in security as evidenced by our analyses and evaluations.